50C Fast‐Charge Li‐Ion Batteries using a Graphite Anode. Issue 43 (23rd September 2022) - Sun, Chuangchao; Ji, Xiao; Weng, Suting; Li, Ruhong; Huang, Xiaoteng; Zhu, Chunnan; Xiao, Xuezhang; Deng, Tao; Fan, Liwu; Chen, Lixin; Wang, Xuefeng; Wang, Chunsheng; et al.
Abstract: Li‐ion batteries have made inroads into the electric vehicle market with high energy densities, yet they still suffer from slow kinetics limited by the graphite anode. Here, electrolytes enabling extreme fast charging (XFC) of a microsized graphite anode without Li plating are designed. Comprehensive characterization and simulations on the diffusion of Li + in the bulk electrolyte, charge‐transfer process, and the solid electrolyte interphase (SEI) demonstrate that high ionic conductivity, low desolvation energy of Li +, and protective SEI are essential for XFC. Based on the criterion, two fast‐charging electrolytes are designed: low‐voltage 1.8 m LiFSI in 1, 3‐dioxolane (for LiFePO4 ||graphite cells) and high‐voltage 1.0 m LiPF6 in a mixture of 4‐fluoroethylene carbonate and acetonitrile (7:3 by vol) (for LiNi0.8 Co0.1 Mn0.1 O2 ||graphite cells). The former electrolyte enables the graphite electrode to achieve 180 mAh g −1 at 50C (1C = 370 mAh g −1 ), which is 10 times higher than that of a conventional electrolyte. The latter electrolyte enables LiNi0.8 Co0.1 Mn0.1 O2 ||graphite cells (2 mAh cm −2, N/P ratio = 1) to provide a record‐breaking reversible capacity of 170 mAh g −1 at 4C charge and 0.3C discharge. This work unveils the key mechanisms for XFC and provides instructive electrolyte design principles for practical fast‐charging LIBs with graphite anodes. Abstract : The electrochemical kinetics for Li + transport will be dramatically enhanced by the rational design of electrolytes with low Δ E dsv of Li +, high ionic conductivities, as well as the ability to form thin and robust solid electrolyte interphase on the graphite surfaces. Following the criterion, 50C fast‐charge Li‐ion batteries using graphite anode are successfully developed.